EDUKASI OSTEOARTHRITIS (OA) DENGAN INTERVENSI E-BOOKLET BAGI JAMAAH AL MANSHUURIN KELURAHAN YABANSAI, DISTRIK HERAM KOTA JAYAPURA, PAPUA - Mulyono, Herlambang Budi; Jembise, Trajanus L.; Iswanto, Dais (JURNAL PENGABDIAN PAPUA, 2024)
Osteoarthritis (OA) counseling has an important urgency for the community because it increases public knowledge about osteoarthritis. In addition, osteoarthritis counseling helps increase public knowledge about osteoarthritis, including symptoms, causes, and how to prevent and treat it. With adequate knowledge, people will more easily recognize the signs of osteoarthritis and choose the right way to prevent or treat it so that the quality of life is better. The activity method is carried out with lectures, answers and digital distribution of osteoarthritis e-booklets to the community so that the material is easy to store and learn more. The results of the evaluation activity showed an increase in participants' knowledge about OA disease after participating in the activity. This shows that the service activities provide significant benefits in increasing participants' awareness and understanding of OA disease. However, long-term evaluation is still needed to see the broader impact on participants' behaviors and attitudes regarding the prevention and management of OA disease.